(3MGTjI Ydi GdeWhds - (3GdLQLGfj, GdTQja GdLQLGfj, GdLQLGfj, Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj, J (B816(3g` (B1413(3es
(3ChdgG (B:s
(3ChdgG(B: (3CYde Cf aj GHJOGA GdJCdja ddaVdGA SHY WQGFb KdGKI efgG hGLHI GdGSJYeGd cGdHSedI LQJ SfI hGdNda hGdSda HbUOs
(3BNQgG (B:s
(3BNQgG(B: (3Cj bhd UeI Hf YHO Gddg GdUeI GdQLd GdTLGY (B... (3Ch dG jchf dcd cdeI ef EMOi GdbQfjf ebGHd ef GdCNQi fMh EfG CYWjfGc GdchKQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 7s
(3GdPQjYI, L(B6: 53s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdHdGZIs